Pengaruh ICT Literacy Dan Self Directed Learning Terhadap Kemandirian Belajar Mahasiswa Prodi PAP Unesa Di Era Normal - Adinda Gresita; Lifa Farida Panduwinata (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
Students have been forced to study from home because of the covid-19 pandemic. However, lecturers have been expected to be more innovative in guiding and delivering teaching from home, requiring lecturers to work from home (WFH). The presence of digital systems due to technological developments and data that is neither spatially nor temporally constrained can be used to search for learning module data. ICT Literacy enables readers to access information at any time and from any location via features connected to the internet network. ICT literacy is the ability to access, organize, integrate, evaluate, generate, and transmit data to contribute to knowledge. Apart from ICT, another factor contributing to student learning independence is Self-Directed Learning  (SDL). Self-directed learning is when a student uses their knowledge in the form of initiatives to take responsibility for their lessons, with or without the help of others. This involves comprehending points of view, practice strategies, practice activities, assessments, and interpersonal skills. By combining ICT literacy with SDL, students’ learning resources can be enriched, resulting in increased learning independence. This study employs associative research with a quantitative approach.  The data were analyzed using the Partial T-Test and Simultaneous F-Test. This research shows that ICT literacy, self-directed learning, and the learning independence of students in the Office Administration Education study program in 2021 and 2022 all have a positive effect.